HUBUNGAN KESENJANGAN PILIHAN FERTILITAS DAN RELASI KUASA SUAMI ISTRI DENGAN UNMET NEED KELUARGA BERENCANA (KB): ANALISIS DATA SDKI 2007 - , Nurul Fitriyah; , dr. Siswanto Agus Wilopo, SU., M.Sc., Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: In Indonesia the achievement of Contraceptive Prevalence Rate (CPR) is increasing and, unfortunately, so is unmet need for contraception. Differences in fertility preferences and husband-wife power relations are supposed to be the causes of unmet need for contraception. Objective: To analyze the relationship between differences in fertility preferences and husband-wife power relations and unmet need for contraception in Indonesia. Method: This survey study with cross-sectional study design used 2007 IDHS data. Subjects were monogamous couples, consisting of married men and women aged 15-54 years and 15-49 years, respectively. Chisquare statistical test and logistic regression test were used with Confidence Interval (CI) 95% and p<0.05. Result: Of 7464 couples, it was found that husbandsâ, wivesâ, and couplesâ unmet need for contraception was 5.5%, 8.1%, and 9.8%, respectively. The prevalence of husbandsâ, wivesâ, and couplesâ unmet need for contraception was greater in husbandsâ fertility preferences. Factors related to husbandsâ unmet need for contraception in regard to husbandsâ fertility preferences (OR=1.4